2020
DOI: 10.1002/jbt.22441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citronellol on NF‐kB inflammatory signaling molecules in chemical carcinogen‐induced mammary cancer in the rat model

Abstract: Inflammation plays a vital role in the process of carcinogenesis and anti‐inflammatory properties of phytochemicals are gaining more attention in the chemoprevention of cancer. The present study was designed to evaluate the anti‐inflammatory potential of citronellol (CT) on 7,12‐dimethylbenz(a)anthracene (DMBA)‐induced mammary carcinogenesis in rats. The inflammation‐associated gene and protein markers were analyzed by immunohistochemistry, reverse transcription polymerase chain reaction, and Western blot tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…It is believed that the lncRNA UCA1 induces the migration and invasion of thyroid cancer cells via miR-497-3p downregulation [272]. On the other hand, the lncRNA UCA1 reduces the expression of miR-654-5p to upregulate the expression of salt-inducible kinase 2 (SIK2), which leads to the development of PTX resistance [273]. In addition, other lncRNAs such as GAS8-AS1 can inhibit the lncRNA UCA1 to suppress the invasion of osteosarcoma cells [274].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the lncRNA UCA1 induces the migration and invasion of thyroid cancer cells via miR-497-3p downregulation [272]. On the other hand, the lncRNA UCA1 reduces the expression of miR-654-5p to upregulate the expression of salt-inducible kinase 2 (SIK2), which leads to the development of PTX resistance [273]. In addition, other lncRNAs such as GAS8-AS1 can inhibit the lncRNA UCA1 to suppress the invasion of osteosarcoma cells [274].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…Nuclear factor-kappaB (NF-κB) is a transcription factor associated with pathological events including inflammation and cancer [112,273,[276][277][278][279][280][281]. The IκB kinase (IKK) is an upstream mediator of NF-κB that is capable of regulating the proliferation and migration of cancer cells [282][283][284][285][286][287][288].…”
Section: Nuclear Factor-κb (Nf-kb) Signaling Pathwaymentioning
confidence: 99%
“…The reduced NF-kB levels in the following study can perhaps be explained by the theoretical means: that cisplatin tends to cause NF-kB inhibition by binding the regions of “kB” that are the binding regions of NF-kB [ 51 ]. The expression of COX-2 which is linked to the proliferation of cells is mediated by the activated NF-kB [ 76 ]. The levels of TNF-α, IL-1β, and NF-kB were upregulated in cisplatin-treated rats in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A study on esophageal squamous cell carcinoma reported that the extracellular S100A14 protein binds to RAGE receptor (receptor for advanced glycation end products) leading to modulating of RAGE signaling, as the engagement of RAGE with S100A14 triggers activation of mitogen activated protein (MAP) kinase and nuclear factor κB (NF-κB) signaling pathways [2]. While the over signaling of MAP kinase pathway causes altering in cell proliferation and survival to an abnormal manner, NF-κB-signaling pathway establishes a microenvironment which is crucial for either cancer initiation or development, or both by increasing cellular metabolic activity and cell division [22]. Another study identified CCL2 (chemokine (C-C motif) ligand 2) as a downstream target of S100A14.…”
Section: Discussionmentioning
confidence: 99%